Cobalt-free maraging steel laser cladding wire as well as preparation method and application thereof
The laser cladding wire of cobalt-free martensite aging steel is prepared by melting the mixed powder and applying a wire feeding laser cladding process, the problem of defects such as cracks and pores in the existing technology of cobalt-free martensite aging steel laser cladding is solved, and its tensile strength and hardness are significantly improved.
Patent Information
- Application Number
- CN202411951978.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, the cobalt-free martensite aging steel is prepared by laser cladding through mixed powder, which has defects such as cracks and pores, which affects its performance.
By drawing the ingots obtained after the mixed powder are melted through the drawing process, a cobalt-free martensite aging steel laser cladding wire is prepared, and laser cladding is performed by wire feeding to reduce defects.
It effectively avoids cracks and pore defects, improves the tensile strength and hardness of cobalt-free martensite aging steel, so that its tensile strength is greater than 1850MPa and hardness is greater than 58HRC.
Smart Images

Figure CN119592882A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of steel material preparation, and in particular relates to a cobalt-free martensitic aging steel laser cladding wire and a preparation method and application thereof. Background Art
[0002] Maraging steel has been widely used in rocket engine casings, aircraft landing gear, uranium enrichment centrifuges and ultra-high pressure vessels due to its excellent comprehensive mechanical properties and welding properties. In addition, maraging steel has good structural stability when the temperature changes drastically, and is widely used in precision instruments with special working environments, such as engine rotors and firing pins of automatic weapons. In addition, maraging steel can be found in high-tech fields such as medical equipment, aerospace, and atomic energy.
[0003] As an emerging processing technology, laser cladding has advantages that traditional processing methods do not have, such as no chemical pollution and convenient processing. Therefore, compared with traditional casting, powder metallurgy and other manufacturing processes, the preparation of maraging steel by laser cladding has the advantages of low cost, simple steps, high performance, etc., and has a very broad application prospect.
[0004] At present, there are many studies on the laser cladding process of traditional 18Ni maraging steel C250, C300, C350 and other grades, especially the laser cladding preparation and performance research of C300 accounts for more than 80%. Due to the scarcity of cobalt resources, cobalt-free maraging steel has become the future development direction. The existing technology uses molybdenum instead of cobalt to prepare cobalt-free maraging steel. The laser cladding method of cobalt-free maraging steel usually mixes the various raw materials used to prepare cobalt-free maraging steel to obtain a mixed powder, and the mixed powder is fed by powder to obtain maraging steel under laser cladding. However, the cobalt-free maraging steel prepared by using the mixed powder has defects such as cracks and pores, which seriously affect the performance of the maraging steel. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a cobalt-free maraging steel laser cladding wire and a preparation method and application thereof. By preparing the cobalt-free maraging steel laser cladding wire and performing laser cladding by wire feeding, defects such as cracks and pores in the cobalt-free maraging steel are effectively reduced.
[0006] In order to achieve the above-mentioned purpose, the technical solution of the present invention is specifically as follows.
[0007] A method for preparing a cobalt-free maraging steel laser cladding wire, characterized in that it comprises the following steps:
[0008] After the mixed powder is melted, it is poured into a mold and solidified to form an ingot;
[0009] The ingot is annealed at 1000° C. to 1100° C., and drawn at 800° C. to 850° C. at a speed of 10 mm / min to 15 mm / min and a drawing force of 300 kN to 400 kN to obtain a cobalt-free maraging steel laser cladding wire;
[0010] The mixed powder is prepared from the following components in terms of mass percentage:
[0011] The Ni element content is 16wt% to 20wt%, the Mo element content is 5wt% to 8wt%, the Ti element content is 0.5wt% to 2.5wt%, the Al element content is 0.05wt% to 0.15wt%, the C, P, and S element contents are all not more than 0.01wt%, the Si and Mn element contents are both not more than 0.1wt%, and the rest is Fe element, totaling 100%.
[0012] The invention processes the billet obtained by smelting the mixed powder through a drawing process, and obtains a cobalt-free maraging steel laser cladding wire with uniform and dense structure, no defects, and high precipitate phase density, which can effectively avoid defects such as cracks and pores in the maraging steel obtained by laser cladding with mixed powder in the prior art.
[0013] In another preferred embodiment, the diameter of the cobalt-free maraging steel laser cladding wire is 10 mm to 16 mm.
[0014] In another preferred embodiment, the smelting temperature is 1800°C to 1900°C.
[0015] A second aspect of the present invention provides the cobalt-free maraging steel laser cladding wire.
[0016] The third aspect of the present invention provides the use of the cobalt-free maraging steel laser cladding wire in the preparation of cobalt-free maraging steel.
[0017] A fourth aspect of the present invention provides a method for preparing cobalt-free maraging steel, comprising the following steps:
[0018] The cobalt-free maraging steel laser cladding wire is subjected to a laser cladding operation at 1000W to 3000W and a scanning speed of 200mm / s to 500mm / s to obtain a primary product;
[0019] The primary product is subjected to secondary laser cladding at 2000W to 2500W and a scanning speed of 1000mm / s to 2000mm / s to obtain the cobalt-free maraging steel.
[0020] In another preferred embodiment, the overlap rate of the laser cladding is 40% to 50%, and the spot diameter is 1 mm to 3 mm.
[0021] In another preferred embodiment, the overlap rate of the secondary laser cladding is 10% to 30%, and the spot diameter is 2 mm to 2.5 mm.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] In the present invention, the ingot obtained by smelting the mixed powder is subjected to a drawing process to obtain the cobalt-free maraging steel laser cladding wire, which has a uniform and dense structure without defects and a high density of precipitated phases. Therefore, the cobalt-free maraging steel laser cladding wire can effectively avoid the defects of cracks and pores in the cobalt-free maraging steel obtained by laser cladding of the mixed powder in the prior art, and effectively improves the tensile strength and hardness of the cobalt-free maraging steel.
[0024] In the process of preparing cobalt-free maraging steel by laser cladding, the present invention adopts a synchronous wire feeding method, abandons the common powder feeding process of traditional laser cladding, and through two laser claddings, the molten pool is quickly solidified again, the grains of the cladding layer are refined, the growth of precipitated phases such as Ni3Mo, Fe2Mo and η-Ni3Ti is inhibited, the performance is effectively improved, and preparation defects such as component segregation, cracks, pores, inclusions, oxides, etc. are eliminated.
[0025] The cobalt-free maraging steel laser cladding wire of the present invention is obtained by a method of twice laser cladding, and the tensile strength of the cobalt-free maraging steel is greater than 1850 MPa and the hardness is greater than 58 HRC. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a microstructure diagram of the cobalt-free maraging steel laser cladding welding wire in Example 1 of the present invention.
[0027] Figure 2 This is a microstructure diagram of the mixed powder of the cobalt-free maraging steel before melting and drawing in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The technical solutions in the present invention will be described clearly and completely below in conjunction with the specific implementation of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The methods described in the embodiments of the present invention are conventional methods unless otherwise specified. The materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified.
[0030] At present, there are many studies on the laser cladding process of traditional 18Ni maraging steel C250, C300, C350 and other grades, especially the laser cladding preparation and performance research of C300 accounts for more than 80%. Due to the scarcity of cobalt resources, cobalt-free maraging steel has become the future development direction, and the existing technology uses molybdenum to replace cobalt. However, when the composition of maraging steel changes, especially the molybdenum element increases significantly, and the cobalt element is removed, the various raw materials used to prepare maraging steel are usually mixed to obtain a mixed powder, and the mixed powder is laser clad to obtain maraging steel. However, the five-grain maraging steel prepared by the mixed powder method has defects such as cracks and pores, which seriously affect the performance of maraging steel.
[0031] The present invention prepares a cobalt-free maraging steel laser cladding wire by subjecting a billet obtained by smelting a mixed powder to a drawing process, thereby effectively avoiding defects such as cracks and pores existing in the cobalt-free maraging steel prepared by a traditional powder feeding method, and inhibiting the growth of precipitated phases such as Ni3Mo, Fe2Mo and η-Ni3Ti through a secondary laser cladding method, thereby further improving the mechanical properties of the cobalt-free maraging steel, making the tensile strength greater than 1850MPa and the hardness greater than 58HRC.
[0032] The following is a detailed description of a cobalt-free maraging steel laser cladding wire and its preparation method and application.
[0033] Example 1
[0034] A method for preparing a cobalt-free maraging steel laser cladding wire comprises the following steps:
[0035] S1. After melting the mixed powder at 1850°C, pour it into a cylindrical mold and solidify it to form an ingot. In terms of mass fraction, the mixed powder consists of the following raw materials:
[0036] The Ni element content is 20wt%, the Mo element content is 8wt%, the Ti element content is 2.5wt%, the Al element content is 0.15wt%, the C, P, and S element contents are all 0.01wt%, the Si and Mn element contents are all 0.1wt%, and the rest is Fe element, totaling 100%.
[0037] S2. After the ingot is annealed at 1000°C, the annealed ingot is placed in a drawing machine, and drawn at 850°C, at a speed of 10 mm / min, for 10 h, and with a pulling force of 400 kN to obtain a cobalt-free maraging steel laser cladding wire with a diameter of 16 mm.
[0038] Example 2
[0039] A method for preparing a cobalt-free maraging steel laser cladding wire comprises the following steps:
[0040] S1. After melting the mixed powder at 1800°C, pour it into a mold and solidify it to form an ingot.
[0041] According to the mass fraction, the mixed powder is composed of the following raw materials:
[0042] The Ni element content is 18wt%, the Mo element content is 7.5wt%, the Ti element content is 2wt%, the Al element content is 0.12wt%, the C, P, and S element contents are all 0.005wt%, the Si and Mn element contents are all 0.05wt%, and the rest is Fe element, totaling 100%.
[0043] S2. After the ingot is annealed at 1050°C, the annealed ingot is placed in a drawing machine and drawn at 820°C at a speed of 12 mm / min for 8 hours and a drawing force of 370 kN to obtain a cobalt-free maraging steel laser cladding wire with a diameter of 16 mm.
[0044] Example 3
[0045] A method for preparing a cobalt-free maraging steel laser cladding wire comprises the following steps:
[0046] S1. After melting the mixed powder at 1900°C, pour it into a mold and solidify it to form an ingot.
[0047] According to the mass fraction, the mixed powder is composed of the following raw materials:
[0048] The Ni element content is 17wt%, the Mo element content is 6wt%, the Ti element content is 1.5wt%, the Al element content is 0.08wt%, the C, P, and S element content are all 0.01wt%, the Si and Mn element content are all 0.1wt%, and the rest is Fe element, totaling 100%.
[0049] S2. After the billet is annealed at 1050°C, the annealed billet is placed in a drawing machine and drawn at 820°C at a speed of 12 mm / min for 8 hours and a drawing force of 340 kN to obtain a cobalt-free maraging steel laser cladding wire with a diameter of 12 mm.
[0050] Example 4
[0051] A method for preparing a cobalt-free maraging steel laser cladding wire comprises the following steps:
[0052] S1. After melting the mixed powder at 1850°C, pour it into a mold and solidify it to form an ingot.
[0053] According to the mass fraction, the mixed powder is composed of the following raw materials:
[0054] The Ni element content is 16wt%, the Mo element content is 5wt%, the Ti element content is 0.5wt%, the Al element content is 0.05wt%, the C, P, and S element contents are all 0.01wt%, the Si and Mn element contents are all 0.1wt%, and the rest is Fe element, totaling 100%.
[0055] S2. After the ingot is annealed at 1100°C, the annealed ingot is placed in a drawing machine and drawn at 800°C at a speed of 10 mm / min for 10 h and a drawing force of 300 kN to obtain a cobalt-free maraging steel laser cladding wire with a diameter of 10 mm.
[0056] The microstructure analysis of the mixed powder and the cobalt-free maraging steel laser cladding wire in Example 1 was performed. Figure 1 and Figure 2 As shown. Figure 1 and Figure 2 It can be seen that compared with the mixed powder, the cobalt-free maraging steel laser cladding wire obtained after drawing has a uniform and dense structure, no defects, and a high density of precipitated phase. Therefore, the use of cobalt-free maraging steel laser cladding wire for laser cladding can further improve the mechanical properties of cobalt-free maraging steel and reduce defects such as cracks and pores.
[0057] The cobalt-free maraging steel laser cladding wires prepared in Examples 1 to 4 all have comparable effects. The cobalt-free maraging steel laser cladding wire in Example 1 is used for laser cladding to prepare cobalt-free maraging steel.
[0058] Example 5
[0059] A method for preparing cobalt-free maraging steel comprises the following steps:
[0060] S1. The cobalt-free maraging steel laser cladding wire in Example 1 is subjected to a laser cladding operation at 1000 W, a scanning speed of 200 mm / s, an overlap rate of 40%, and a spot diameter of 1 mm to obtain a primary product.
[0061] S2. The primary product was subjected to secondary laser cladding under the conditions of 2000 W, a scanning speed of 1000 mm / s, an overlap rate of 10%, and a spot diameter of 2 mm to obtain cobalt-free maraging steel.
[0062] Example 6
[0063] A method for preparing cobalt-free maraging steel comprises the following steps:
[0064] S1. The cobalt-free maraging steel laser cladding wire in Example 1 is subjected to a laser cladding operation at 2000 W, a scanning speed of 350 mm / s, an overlap rate of 45%, and a spot diameter of 2 mm to obtain a primary product.
[0065] S2. The primary product was subjected to secondary laser cladding under the conditions of 2300 W, a scanning speed of 1500 mm / s, an overlap rate of 20%, and a spot diameter of 2.3 mm to obtain cobalt-free maraging steel.
[0066] Example 7
[0067] A method for preparing cobalt-free maraging steel comprises the following steps:
[0068] S1. The cobalt-free maraging steel laser cladding wire in Example 1 is subjected to a laser cladding operation at 1000 W, a scanning speed of 500 mm / s, an overlap rate of 50%, and a spot diameter of 3 mm to obtain a primary product.
[0069] S2. The primary product was subjected to secondary laser cladding under the conditions of 2500 W, a scanning speed of 2000 mm / s, an overlap rate of 30%, and a spot diameter of 2.5 mm to obtain cobalt-free maraging steel.
[0070] The cobalt-free maraging steels prepared in Examples 5 to 7 and the cobalt-free maraging steels prepared using the mixed powder in Example 1 by the powder feeding method were used as a control group to measure tensile strength and hardness. The results are shown in Table 1.
[0071] Table 1 Tensile strength and hardness test results
[0072] Group Tensile strength(MPa) Hardness(HRC) Example 5 >1850 >58 Example 6 >1880 >60 Example 7 >1900 >62 Control group >1650 >50
[0073] From the results in Table 1, it can be seen that compared with the control group, the tensile strength and hardness of the cobalt-free maraging steel obtained in Examples 5 to 7 of the present invention are significantly improved, and the improvement effect of the cobalt-free maraging steel in Example 6 is the highest. It can be seen that the present invention uses the cobalt-free maraging steel laser cladding wire through two laser claddings to make the molten pool solidify again quickly, refine the cladding layer grains, and inhibit the growth of precipitated phases such as Ni3Mo, Fe2Mo and η-Ni3Ti, thereby eliminating preparation defects such as component segregation, cracks, pores, inclusions, oxides, etc., and effectively improves the tensile strength and hardness of the cobalt-free maraging steel obtained by laser cladding using the powder feeding method.
[0074] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a cobalt-free maraging steel laser cladding wire, characterized in that: The following steps are involved: After the mixed powder is melted, it is poured into a mold and solidified to form an ingot; After annealing the ingot at 1000° C. to 1100° C., the ingot is drawn at 800° C. to 850° C. at a speed of 10 mm / min to 15 mm / min and a drawing force of 300 kN to 400 kN to obtain a cobalt-free maraging steel laser cladding wire; The mixed powder is prepared from the following components in terms of mass percentage: The Ni element content is 16wt% to 20wt%, the Mo element content is 5wt% to 8wt%, the Ti element content is 0.5wt% to 2.5wt%, the Al element content is 0.05wt% to 0.15wt%, the C, P, and S element contents are all not more than 0.01wt%, the Si and Mn element contents are both not more than 0.1wt%, and the rest is Fe element, totaling 100%.
2. The method for preparing the cobalt-free maraging steel laser cladding wire according to claim 1, characterized in that: The diameter of the cobalt-free maraging steel laser cladding wire is 10 mm to 16 mm.
3. The method for preparing the cobalt-free maraging steel laser cladding wire according to claim 1, characterized in that: The smelting temperature is 1800°C to 1900°C.
4. A cobalt-free maraging steel laser cladding wire prepared according to the preparation method according to any one of claims 1 to 3.
5. Use of the cobalt-free maraging steel laser cladding wire according to claim 4 in the preparation of cobalt-free maraging steel.
6. A method for preparing cobalt-free maraging steel, characterized in that: The following steps are involved: The cobalt-free maraging steel laser cladding wire according to claim 4 is subjected to a laser cladding operation at 1000W to 3000W and a scanning speed of 200mm / s to 500mm / s to obtain a primary product; The primary product is subjected to secondary laser cladding at 2000W to 2500W and a scanning speed of 1000mm / s to 2000mm / s to obtain the cobalt-free maraging steel.
7. The method for preparing cobalt-free maraging steel according to claim 6, characterized in that: The overlap rate of the primary laser cladding is 40% to 50%, and the spot diameter is 1 mm to 3 mm.
8. The method for preparing cobalt-free maraging steel according to claim 6, characterized in that: The overlap rate of the secondary laser cladding is 10% to 30%, and the spot diameter is 2 mm to 2.5 mm.